COVID-19 breakthrough infections in type 1 diabetes mellitus: a cross-sectional study by the COVID-19 Vaccination in Autoimmune Diseases (COVAD) Group - Panchawagh, Suhrud; Ravichandran, Naveen; Barman, Bhupen; Nune, Arvind; Javaid, Mahnoor; Gracia-Ramos, Abraham Edgar; Day, Jessica; Joshi, Mrudula; Kuwana, Masataka; Saha, Sreoshy; Pande, Arunkumar R.; Caballero-Uribe, Carlo Vinicio; et al. (Rheumatology International, 2024)
To investigate the frequency, profile, and severity of COVID-19 breakthrough infections (BI) in patients with type I diabetes mellitus (T1DM) compared to healthy controls (HC) after vaccination. The second COVID-19 Vaccination in Autoimmune Diseases (COVAD-2) survey is a multinational cross-sectional electronic survey which has collected data on patients suffering from various autoimmune diseases including T1DM. We performed a subgroup analysis on this cohort to investigate COVID-19 BI characteristics in patients with T1DM. Logistic regression with propensity score matching analysis was performed. A total of 9595 individuals were included in the analysis, with 100 patients having T1DM. Among the fully vaccinated cohort, 16 (16%) T1DM patients had one BI and 2 (2%) had two BIs. No morbidities or deaths were reported, except for one patient who required hospitalization with oxygen without admission to intensive care. The frequency, clinical features, and severity of BIs were not significantly different between T1DM patients and HCs after adjustment for confounding factors. Our study did not show any statistically significant differences in the frequency, symptoms, duration, or critical care requirements between T1DM and HCs after COVID-19 vaccination. Further research is needed to identify factors associated with inadequate vaccine response in patients with BIs, especially in patients with autoimmune diseases.
CRIS-Team Scopus Importer:2024-01-12
Keywords: Breakthrough infections; COVID-19; Survey; Type 1 diabetes mellitus; Vaccine